The Effectiveness of Employee Discipline Culture at the Office of the Environment and Forestry Office of Sinjai Regency - Jamaluddin Jamaluddin; Baswal Baswal; Sirajuddin Saleh; Muhammad Darwis; Muh. Nasrullah (Universitas Negeri Makassar, 2021)
The culture of employee work discipline is used as a habit of self-actualization in realizing attitudes and behaviors that can reflect obedience and compliance with the regulations that have been set by the organization to create quality employees. Research objectives to determine an overview of the effectiveness level of employee discipline culture in the Office of the Environment and Forestry Office of Sinjai Regency and the supporting factors and inhibiting factors of the effectiveness of the employee work discipline culture. This research uses quantitative methods. Data collection techniques are observation, questionnaire, interview, and documentation techniques. Analysis of the data presented through the frequency table and processed through the technique of calculating scores. The data analysis technique in this study uses the percentage formula. The results showed that the level of effectiveness of the employee discipline culture was in the very effective category in terms of punctuality, using office equipment properly. This research can be used as a reference to determine the level of work discipline and awareness of employees at the Office of the Environment and Forestry Office of Sinjai Regency. Because there are still employees who still do not comply with the regulations that have been set.